Affective Clamor - Janelle Schwartz (Humanimalia, 2016)
Tobias Menely, The Animal Claim: Sensibility and the Creaturely Voice. Chicago: The University of Chicago Press, 2015. 280pp. $90.00 hb; $30.00 pb.